Dominican Republic, Central American Free Trade Agreement (DR-CAFTA) : Challenges and Opportunities for Central America - World Bank (Washington, DC, 2012)
This report provides a preliminary assessment of DR-CAFTA (the , with particular attention to three key themes: (1) expected trade and non-trade benefits, (2) actions that Central American countries need to pursue to capitalize optimally on the new opportunities, and (3) identification of the population groups that may require assistance to adapt to a more competitive environment. The report focuses on the developing countries of Central America, namely Costa Rica, El Salvador, Guatemala, Honduras, and Nicaragua. The analysis presented in the report shows that the vast majority of the population in Central America is likely to experience welfare gains from implementation of DR-CAFTA, even in the short run. At the same time, the removal of trade barriers in sensitive agricultural crops could adversely affect a small share of the population living in rural areas in Central America. Although provisions in DR-CAFTA will allow for long timetables in reducing tariffs for the most sensitive products, appropriate support programs may need to be designed. In addition, selective investments in education, rural infrastructure, rural finance, and technical assistance will be required to ensure that the rural poor have the means to take full advantage of the new opportunities arising out of DR-CAFTA. Chapter 1 of the report reviews the main findings of the chapters in the order in which they appear. Chapter 2 places DR-CAFTA in the historical context of the economic reforms that Central American countries have been undertaking since the late 1980s. Chapter 3 provides a summary overview of the recently negotiated DR-CAFTA, with special attention on the extent to which the agreement's provisions would significantly change market access for Central American goods and services, and also on how far they could be expected to consolidate prior reforms. Chapter 4 reviews various analyses that assess the potential impacts of DR-CAFTA on the developing countries of Central America. Chapter 5 focuses on the identification and quantification of potentially affected populations from the easing of trade restrictions in sensitive agricultural products, and analyzes policy options to assist vulnerable groups. Chapter 6 reviews evidence related to key macroeconomic implications of DR-CAFTA, namely the potential revenue losses that might be produced by the removal of import taxes and the treaty's potential effect on the patterns of business-cycle synchronization. Chapter 7 reviews evidence from each Central American country in the areas of trade facilitation, institutional and regulatory reforms, and innovation and education, in order to identify key priorities for the complementary agenda for DR-CAFTA.